2019
DOI: 10.1002/htj.21616
|View full text |Cite
|
Sign up to set email alerts
|

Rotational speed adjustment of axial flow fans to maximize net power output for direct dry cooling power generating units

Abstract: The power consumption of axial flow fans may account for more than 1% of the rated power output of the power generating unit, so it is of benefit to the energy efficiency of the power generating unit to propose an operation adjustment approach to axial flow fans. On the basis of representative 2 × 600 MW direct dry cooling generating units, a computational model of air-side flow and heat transfer of an air-cooled condenser (ACC) combined with exhaust steam condensation is developed, by which the airflow rate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…When the operating states of fans change, their characteristic parameters will vary accordingly. For a certain fan, the variations in the parameters obey the similarity principle as follows when only the rotational speed changes [33].…”
Section: Mathematical Models and Methodsmentioning
confidence: 99%
“…When the operating states of fans change, their characteristic parameters will vary accordingly. For a certain fan, the variations in the parameters obey the similarity principle as follows when only the rotational speed changes [33].…”
Section: Mathematical Models and Methodsmentioning
confidence: 99%
“…The windward surface of the computational domain was established as the velocity inlet boundary condition, the domain outlet was set as the pressure outlet boundary condition, and symmetric boundary conditions were adopted for the remaining surfaces when there was ambient wind. Equation (1) 22,23 was used to calculate the wind speed at a height above ground.…”
Section: Research Preparationmentioning
confidence: 99%
“…The windward surface of the computational domain was established as the velocity inlet boundary condition, the domain outlet was set as the pressure outlet boundary condition, and symmetric boundary conditions were adopted for the remaining surfaces when there was ambient wind. Equation (1) 22,23 was used to calculate the wind speed at a height above ground. vi=v10zi10m, ${v}_{i}={v}_{10}{\left(\frac{{z}_{i}}{10}\right)}^{m},$where v 10 (m/s) denotes wind speed at the height of 10 m. Any height, m , was denoted by z i (m); the ground roughness coefficient, m , which in this work was chosen to be 0.16; and the wind speed at z i was v i (m/s).…”
Section: Research Preparationmentioning
confidence: 99%
“…Considering the dynamic variations within axial flow fan arrays, numerous researchers have directed their attention towards transitioning from the conventional unified control of fan groups to the par-titioned adjustment of axial flow fans. Chen [10] divided the 7 × 16 fan array into two zones and found that increasing the speed in the windward zone can significantly increase the output of the unit. In paper [11], for a 5 × 12 fan array, the fans are divided into six constituencies by column, and four speed strategies are designed.…”
Section: Introductionmentioning
confidence: 99%